Humoral and cellular response to SARS-CoV-2 mRNA vaccine in paediatric heart transplant recipients - Amanda Bermejo-Gómez; Laura Tarancon-Diez; Beatriz Lazaro-Martin; Begoña Santiago-Garcia; Nuria Gil Villanueva; Roberto Alonso; Mª Ángeles Muñoz-Fernández; Manuela Camino López; Alicia Hernanz-Lobo; María Luisa Navarro Gómez (Heliyon)
Objective: The aim of this prospective cohort study is to analyse the humoral and cellular vaccine responses in paediatric heart transplant recipients (HTR, n = 12), and compare it with the response in healthy controls (HC, n = 14). All participants were 5–18 years old and vaccinated with mRNA vaccine against SARS-CoV-2 between December 2021 and May 2022. Methods: The humoral response was measured by quantifying antibody titers against SARS-CoV-2 spike protein (anti-S). The T-lymphocyte phenotype and SARS-CoV2-specific CD4+ and CD8+ T-cell response was studied by multiparametric flow cytometry through peripheral blood mononuclear cells by the quantification of degranulation markers (CD107a) and intracellular cytokines (IFN-γ, TNF-α and IL-2) after in vitro stimulation with SARS-CoV-2 peptides from structural proteins (S, M, N, E) and non-structural viral proteins. Results: After vaccination, humoral response was found in all HTR, although they showed lower levels of anti-S IgG compared to HC (p = 0.003). However, in terms of cellular response, no significant differences were obtained in the prevalence of responders and magnitude of responses between groups. In addition, anti-S IgG levels directly correlated with a higher SARS-CoV-2 specific T-cell response (rho = 0.43; p = 0.027 and rho = 0.45; p = 0.02 for IFN-γ+ and TNF-α+ production of CD8+ T-cells, respectively). Activated T-cell phenotype in HTR was associated with a lower humoral response to SARS-CoV-2 vaccine. Conclusion: HTR had humoral response after vaccination, although they showed lower levels of specific anti-S antibodies compared to HC. There were no significant differences in the SARS-CoV2-specific cellular response between the two groups. Obtaining satisfactory data on this type of response could potentially challenge the current vaccine guideline recommendations.